Some blood values in cows diagnosed clinically as ephemeral fever: Jameel G.H.1 ; Hasan A. SH.2 ; Jawad S.J.1 - H., Jameel G. (The Iraqi Journal of Veterinary Medicine, 2012)
Sixty cows were included in this study which was conducted in Baquba for the period from April 2011 to October 2011. They were clinically diagnosed as having bovine ephemeral fever (BEF) infection. Blood samples were collected from infected cows before, after treatment, and after recovery. Additionally, 30 healthy cows were included as control group. Sera were separated and submitted for the determination of phosphorus, glucose, cholesterol and pH levels. Statistical analysis of biochemical values revealed significant decrease in serum cholesterol levels in infected cows as compared to control group (P<0.05). Furthermore, the diseased cows showed low levels of pH (acidosis), thus when they treated by intravenous injection of 5% sodium bicarbonate, the signs were rapidly subsided and the cows were completely recovered.